G105(P) Management and follow-up for children with ovarian mature teratomas. (24th May 2017) - Kane, C; Jackson, C; Farrell, S; Baldwin, P; Arul, S; Nicholson, J; Murray, M
Abstract : Aims: Recent concerns have been raised regarding long-term fertility-risk of oophorectomy in children with benign ovarian mature-teratomas (MTs), particularly as contralateral metachronous disease occurs in 20% (Taskinen, 2014). Here we evaluate management of MT, including surgical approach (oophorectomy vs. ovarian-sparing-cystectomy=OSC) and produce an algorithm for post-operative-monitoring. Methods: 10 year single-centre retrospective analysis of ovarianMT patients<16y (Addenbrooke's Hospital, Cambridge; 2006–16). We recorded age/presentation/pre-operative tumour-markers (AFP/HCG) and imaging/tumour-size/MDT discussion/surgical approach/follow-up, and conducted a literature review. Results: Thirty-eight patients with ovarian masses were identified; 14 exclusions (3 records unavailable/11 other pathology). The 24 inclusions comprised 17 patients with histological confirmation of MT and 7 cases with typical pre-operative radiological appearances of MT but uninformative histology (complete post-torsionnecrosis). Pre-operatively, 19 patients (79%) had USS (nine also had 3Dimaging: two CT/seven MRI) and four (17%) had 3D-imaging only (one CT/three MRI). One MT (4%) was identified intraoperatively (suspected appendicitis). Serum AFP and HCG was measured in 19/24 (79%) and 20/24 patients (83%), respectively; there were no pathological elevations. Eleven of 24 patients (46%) were discussed by paediatric-oncology MDT, 1/24 (4%) by gynaecology-MDT, 11/24 by both (46%) and 1/24 (4%) by none. Surgically, 10/24 patients (42%) underwent laparotomy; 14/24 (58%) laparoscopy. Two operations were emergencies. Greater tumour size was weakly associated with laparotomy (p=0.078). Nine of 24 patients (38%) underwent oophorectomy+/-salpingectomy; 15/24 (63%) OSC. Fourteen of 24 (58%) were operated on by paediatric surgeons, 4/24 (17%) by gynaecologists, and 6/24 (25%) jointly. There was no difference in proportion of OSCs by surgical team. In follow-up, there were no recurrences, regardless of surgical approach, but hospital follow-up was generally very short (months). There was no consistency in follow-up protocols; three (13%) had no follow-up, 11 (46%) clinical only and ten (42%) baseline-USS within 6 months of surgery. Of these 10, two of these were discharged to GP for annual/biannual USS-schedules. Conclusion: OSC should always be considered in children presenting with radiological features typical for ovarian MT, normal tumour-markers and no suspicion of malignancy. We have developed a follow-up algorithm based on the presence/absence of symptoms before main presentation, torsion, tumour size and surgical approach. Involvement of shared-care-paediatricians may ensure adherence to follow-up-schedules.